SAT0301 CIRCULATING FIBROCYTES FROM SYSTEMIC SCLEROSIS PATIENTS AS POSSIBLE TARGET OF CTLA4-IG TREATMENT: AN IN VITRO STUDY. (2nd June 2020) - Soldano, S.; Montagna, P.; Paolino, S.; Alessandri, E.; Pizzorni, C.; Pacini, G.; Goegan, F.; Sulli, A.; Schenone, C.; Smith, V.; Cutolo, M.
Abstract : Background: muscle actin (aSMA) + cells involved in the overproduction of extracellular matrix proteins, primarily fibronectin (FN) and type I collagen (COL1) at the level of damaged tissues (1). These cells may originate from different cell types including fibroblasts, endothelial and epithelial cells, and fibrocytes (1). Circulating fibrocytes are bone marrow progenitor cells expressing specific markers of hematopoietic (CD34, CD45, and MHC class II) and stromal cells (COL1 and COL3), chemokine receptors (CCR2, CCR7), and CXCR4 (2). CXCR4 regulates fibrocyte migration into injured tissues allowing their differentiation into fibroblasts/myofibroblasts (2). In vitro, fibrocytes differentiate from circulating CD14 + monocytes showing an antigen-presenting capability through the expression of HLA-DR and costimulatory molecule CD86 (2). CTLA4-Ig fusion protein (abatacept) interacts with CD86 on cell surface of antigen presenting cells (APCs), such as macrophages and endothelial cells (3, 4). Objectives: To investigate the possible effect of CTLA4-Ig treatment on cultured human fibrocytes and skin fibroblasts isolated from the same systemic sclerosis patients (SSc pts). Methods: Fibrocytes isolated from the peripheral blood mononuclear cells of SSc pts and healthy subjects (HSs) were cultured on fibronectin-coated plates in DMEM at 20% of FBS; for further 8 days (T8) to allow their complete differentiation. Differentiated fibrocytes were maintained in growth medium or treated with CTLA4-Ig at different concentrations (10, 50, 100, and 500μg/ml) for 3 hours. Fibroblasts were isolated from the skin biopsies of the same patients and HSs, cultured until the 3 rd passage in RPMI at 10% FBS and then treated with CTLA4-Ig for 24 and 48 hours. Fibrocytes were characterized as CD45 + CXCR4 + COL1 + cells and the expression of CD86 and HLA-DR was also evaluated. The gene expression of aSMA, COL1, CXCR4, TGFb1 and CD86 was investigated by quantitative real-time polymerase chain reaction in cultured fibrocytes and skin fibroblasts. In cultured skin fibroblasts, COL1 and fibronectin synthesis was evaluated by Western blotting. Results: Treatment with CTLA4-Ig for 3 hours significantly downregulated aSMA and COL1 gene expression in cultured SSc fibrocytes at T8 (p<0.01, p<0.05 vs. untreated fibrocytes), whereas no modulatory effect was observed on the TGFbeta1 and CXCR4 gene expression. In cultured SSc skin fibroblasts, CTLA4-Ig did not induce any significant effect on CD68, TGFb1, COL1 and FN gene expression as well as COL1 and FN protein synthesis, both after 24 and 48 hours. Of note, these cultured SSc skin fibroblasts showed a low expression of CD86. Conclusion: Due to their high expression of CD86, circulating fibrocytes seem to be more responsive to CTLA4-Ig treatment than the skin fibroblasts isolated from the same SSc patient. References: [1]Cutolo M et al. Expert Rev Clin Immunol. 2019;15:753-64. [2]Bucala R. Mol Med.2015;2:S3-5. [3]Cutolo M et al. Clin Exp Rheumatol. 2015;33:250-4. [4]Brizzolara R et al. J Rheumatol. 2013;40:738-40. Disclosure of Interests: Stefano Soldano: None declared, Paola Montagna: None declared, Sabrina Paolino: None declared, Elisa Alessandri: None declared, Carmen Pizzorni: None declared, Greta Pacini: None declared, Federica Goegan: None declared, Alberto Sulli Grant/research support from: Laboratori Baldacci, Carlotta Schenone: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Maurizio Cutolo Grant/research support from: Bristol-Myers Squibb, Actelion, Celgene, Consultant of: Bristol-Myers Squibb, Speakers bureau: Sigma-Alpha